MECHANISMS OF IMMUNOSUPPRESSIVE ACTION OF LICORICE ROOT FLAVONOIDS IN CONTACT SENSITIVITY IN MICE: INHIBITION OF T LYMPHOCYTE EFFECTOR FUNCTION MEDIATED BY NON- EFFECTOR CELLS - S. I. Pavlova (SPb RAACI, 2014)
Contact sensitivity is a classical T cell-mediated, clinically important phenomenon elicited by small molecular weight molecules (haptens) that bind to host proteins to form a complete antigen. In our model experiments, contact sensitivity was produced in CBA mice, by means of cutaneous sensitization with 2.4-dinitrofluorobenzene. We used an adoptive transfer of contact sensitivity with different populations of splenocytes, in order to detect immunosuppressive effects of licorice (Glycyrrhizae) root flavonoids. Suppression of adoptive transfer of contact sensitivity in mice-recipients to different degree was found, when applying the flavonoids. It was revealed, that this effect depends on the type of target population interacting with flavonoids. We have also demonstrate, that licorice root flavonoids do not induce apoptosis of effector cells.